Aryl Polyenes, a Highly Abundant Class of Bacterial Natural Products, Are Functionally Related to Antioxidative Carotenoids. Issue 3 (5th January 2016) - Schöner, Tim A.; Gassel, Sören; Osawa, Ayako; Tobias, Nicholas J.; Okuno, Yukari; Sakakibara, Yui; Shindo, Kazutoshi; Sandmann, Gerhard; Bode, Helge B.
Abstract: Bacterial pigments of the aryl polyene type are structurally similar to the well‐known carotenoids with respect to their polyene systems. Their biosynthetic gene cluster is widespread in taxonomically distant bacteria, and four classes of such pigments have been found. Here we report the structure elucidation of the aryl polyene/dialkylresorcinol hybrid pigments of Variovorax paradoxus B4 by HPLC‐UV‐MS, MALDI‐MS and NMR. Furthermore, we show for the first time that this pigment class protects the bacterium from reactive oxygen species, similarly to what is known for carotenoids. An analysis of the distribution of biosynthetic genes for aryl polyenes and carotenoids in bacterial genomes is presented; it shows a complementary distribution of these protective pigments in bacteria. Abstract : Yellow is the new orange ! Here we show the complete structure elucidation of the yellow aryl polyene (APE)/dialkylresorcinol pigments arcuflavins A and B and their in vitro and in vivo function as antioxidants. This function is highlighted by the complementary distribution of APE biosynthetic genes within sequenced bacterial genomes in comparison with carotenoid biosynthesis genes.